The Craft of criticism critical media studies in practice - Kackman, Michael; Kearney, Mary Celeste 1962- (New York Routledge, 2018)
"With contributions from 30 leading media scholars, this collection provides a comprehensive overview of the main methodologies of critical media studies. Chapters address various methods of textual analysis, as well as reception studies, policy, production studies, and contextual, multi-method approaches, like intertextuality and cultural geography. Film and television are at the heart of the collection, which also addresses emergent technologies and new research tools in such areas as software studies, gaming, and digital humanities. Each chapter includes an intellectual history of a particular method or approach, a discussion of why and how it was used to study a particular medium or media, relevant examples of influential work in the area, and an in-depth review of a case study drawn from the author's own research. Together, the chapters in this collection give media critics a complete toolbox of essential critical media studies methodologies"--
Ideology / Ron Becker -- Discourse / Rosalind Gill -- Narrative / Jason Mittell -- Non-fiction media / Daniel Marcus -- Visual style / Jeremy Butler -- Sound / Jacob Smith -- Acting and performance / Cynthia Baron -- Representation / Mary Beltrán -- Authorship and auteurism / Cynthia Chris -- Political economy / Patrick Burkart -- Media policy / Bill Kirkpatrick -- Psychoanalytic criticism / Todd McGowan -- Cognitivism / Ted Nannicelli -- Ethnography / Jessica Lingel & Mary Gray -- Audiences / Matt Hills -- Genre / Amanda Ann Klein -- Intertexts and paratexts / Jonathan Gray -- Stardom and celebrity / Diane Negra & Suzanne Leonard -- Cultural geography / Victoria E. Johnson -- National/transnational/global / Shanti Kumar -- History and historiography / Michael Kackman -- Production / Timothy Havens -- Popular music / Norma Coates -- New media / Madhavi Mallapragada -- Games and gaming / Matthew Thomas Payne & Nina B. Huntemann -- Software / Eric Freedman -- Digital humanities / Miriam Posner.
Includes bibliographical references and index.
Keywords: Mass media criticism